Peningkatan Pemahaman Tentang Promosi Dan Pemanfaatan Aplikasi Editing Di Smartphone Untuk Konten Promosi Digital - Heri Prabowo; Bayu Kurniawan; Sutrisno Sutrisno; Henry Casandra Gultom (jurnal ABDIMAS Indonesia, 2023)
Promotion is a marketing activity that can increase buying interest or influence someone to buy a product and can be an important part of branding a product. One of the products that needs to be increased in promotion is the product of peep craftsmen in Nyatnyono village. Service activities carried out by conducting outreach about promotions and the use of technology in creating promotional content. The activities that have been carried out show that there is an understanding of promotion and use of smartphones for creating content and carrying out promotional activities on social media.